2021
DOI: 10.1111/1751-2980.13041
|View full text |Cite
|
Sign up to set email alerts
|

Per‐oral pancreatoscopy‐guided lithotripsy for the endoscopic management of pancreatolithiasis: A systematic review and meta‐analysis

Abstract: Objective Pancreatic stones result from chronic pancreatitis and can occur in the main pancreatic duct, pancreatic branches or parenchyma. Although extracorporeal shock wave lithotripsy (ESWL) is considered the first‐line treatment, per‐oral pancreatoscopy (POP) has emerged as a useful method for treating pancreatic stones. The aim of this systematic review and meta‐analysis was to determine the efficacy and safety of POP‐guided lithotripsy, electrohydraulic lithotripsy (EHL) and laser lithotripsy (LL), in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(131 reference statements)
0
2
0
1
Order By: Relevance
“…While for LL-POP, the pooled technical and clinical success rate was 88.4% (95% CI 85.9%–95.1%) and 85.8% (95% CI 80.6%–91.6%). In total, 43 adverse events occurred (12.1%;95% CI 8.7%–15.5%) ( 30 ). Another recent meta-analysis of pancreatic duct stone management by McCarty et al showed that in 302 patients, Pooled technical success was 91.18%, with an overall fragmentation success of 85.77%.…”
Section: Discussionmentioning
confidence: 99%
“…While for LL-POP, the pooled technical and clinical success rate was 88.4% (95% CI 85.9%–95.1%) and 85.8% (95% CI 80.6%–91.6%). In total, 43 adverse events occurred (12.1%;95% CI 8.7%–15.5%) ( 30 ). Another recent meta-analysis of pancreatic duct stone management by McCarty et al showed that in 302 patients, Pooled technical success was 91.18%, with an overall fragmentation success of 85.77%.…”
Section: Discussionmentioning
confidence: 99%
“…Mientras que, al comparar entre LHE y láser, los resultados son diversos en relación al sitio de presencia de litos, por un lado, en el metaanálisis de Veld et al, en el que se incluyeron 32 estudios, y que en su mayoría se consideró cálculos biliares en el colédoco, se encontró que la litotricia laser fue superior a EHL, al mostrar mayor tasa de eliminación de cálculos (95,1% frente a 88,4%, respectivamente), y menores tasas de complicaciones post-procedimentales (8,4% vs. 13,8%, respectivamente) (22) . Por el otro, en un metaanálisis reciente, en el que se incluyeron 15 estudios, en sujetos con pancreatolitiasis, Guzmán-Calderón et al encontraron tasa de éxito clínico de LHE del 91,6%, y para laser de 86,6%, y la tasa de eventos adversos fue 12% (23) .…”
Section: Discussionunclassified
“…Adverse events occurred in 12%. 19 The role of intraductal lithotripsy in management of patients with chronic pancreatitis is unclear. Further studies with a head-to-head comparison between ESWL and intraductal lithotripsy may help better define its role.…”
Section: Indications For Cholangioscopymentioning
confidence: 99%